The theoretical background of modernization of physical training content at institutions of higher education - Васьков Юрій Вадимович (Yury Vaskov); Куделко Вікторія Едуардівна (Viktoriya Kudelko); Понікарьова Валентина Григорівна (Valentina Ponikaryova); Болтєнкова Ольга Миколаївна (Olga Boltenkova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to study the problem of designing the content of unprofessional physical training at institutions of higher education. Material and Methods: analysis of regulatory documents and literature on the theory and methodology of physical education. Results: the article deals with the problems of determination the nomenclature of sources and factors that influence the selection and design of physical education’s content, the role and meaningful essence of them are proved, the new approaches to the detection of invariant and variable components of academic curriculum are suggested. Conclusion: the role and brief essence description of particular components of main sources and factors of non-professional sports education are detected, their particular hierarchy and importance are suggested. A variety of sources and design factors of unprofessional sports education is divided into two parts: non-teaching and teaching.